Highly engaged marine users can help monitor marine plastic pollution in under accessed environments - Peter S. Puskic; Isabelle Cramer; Emma Church; Emily Deery; Matthias Egger; Natalie Fox; William P. de Haan; Laurent Lebreton; Arianna Liconti; Anna Sanchez-Vidal; Helen Wolter (Ocean & Coastal Management, 2026)

From the laboratory bench to the lecture hall: latest findings from mycotoxin research presented at the 43rd Mycotoxin Workshop - Olivier Puel; Benedikt Cramer; Isabelle P. Oswald; Hans-Ulrich Humpf (Mycotoxin Research, 2022)

A physiological analogy of the niche for projecting the potential distribution of plants - Steven I. Higgins; Robert B. O’Hara; Olga Bykova; Michael D. Cramer; Isabelle Chuine; Eva‐Maria Gerstner; Thomas Hickler; Xavier Morin; Michael R. Kearney; Guy F. Midgley; Simon Scheiter (Journal of Biogeography, 2012)
Aim To develop a physiologically based model of the plant niche for use in species distribution modelling. Location Europe. Methods We link the Thornley transport resistance (TTR) model with functions which describe how the TTR’s model parameters are influenced by abiotic environmental factors. The TTR model considers how carbon and nutrient uptake, and the allocation of these assimilates, influence growth. We use indirect statistical methods to estimate the model parameters from a high resolution data set on tree distribution for 22 European tree species. Results We infer, from distribution data and abiotic forcing data, the physiological niche dimensions of 22 European tree species. We found that the model fits were reasonable (AUC: 0.79–0.964). The projected distributions were characterized by a false positive rate of 0.19 and a false negative rate 0.12. The fitted models are used to generate projections of the environmental factors that limit the range boundaries of the study species. Main conclusions We show that physiological models can be used to derive physiological niche dimensions from species distribution data. Future work should focus on including prior information on physiological rates into the parameter estimation process. Application of the TTR model to species distribution modelling suggests new avenues for establishing explicit links between distribution and physiology, and for generating hypotheses about how ecophysiological processes influence the distribution of plants.